1985
DOI: 10.1111/j.1365-2125.1985.tb05040.x
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness to oral diazepam in the elderly: relationship to total and free plasma concentrations.

Abstract: 1 The immediate and residual response to single doses of oral diazepam 10 mg was measured in 11 young and 12 elderly healthy volunteers using postural sway, digit symbol substitution scores and subjective ratings. 2 The effect on postural sway was markedly accentuated in the older volunteers, but the difference between groups in the effect on the other measures used did not achieve significance. 3 The corresponding plasma total diazepam concentrations were lower in the older subjects beyond 0.5 h post dose an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 32 publications
0
21
1
Order By: Relevance
“…In a series of experimental trials, Swift et al have found that benzodiazepines impair reaction time and postural sway in elderly people [10,11]. In a previous case-control study of factors associated with injurious falls we also found associations between psychoactive medication use and quadriceps strength, postural sway and two clinical balance measures: static and dynamic balance [12].…”
Section: Introductionmentioning
confidence: 66%
“…In a series of experimental trials, Swift et al have found that benzodiazepines impair reaction time and postural sway in elderly people [10,11]. In a previous case-control study of factors associated with injurious falls we also found associations between psychoactive medication use and quadriceps strength, postural sway and two clinical balance measures: static and dynamic balance [12].…”
Section: Introductionmentioning
confidence: 66%
“…Advancing age is also associated with increased sensitivity to the central nervous system effects of benzodiazepines [115]. Sedation is induced by diazepam at lower doses and lower plasma concentrations in elderly subjects [116,117]. Advancing age is also associated with increased sensitivity to the effects of nitrazepam, flurazepam, and loprazolam [118][119][120].…”
Section: Psychotropic Drugsmentioning
confidence: 99%
“…[1][2][3][4][5][6] Plasma proteins are major contributors to drug binding in blood. Therefore, to better understand the relationship between drug concentrations and pharmacological effects, one must determine the unbound fraction of the total drug concentration.…”
Section: Introductionmentioning
confidence: 99%